Green Synthesis And Characterization Of Iron And Cobalt Oxide Nanoparticles Using Phaseolus Lunatus Flower Extract - Priyanka Ganesh Bhutekar; Anita Kashinath Kshirsagar; Shital Shivaji Bankar; Sunil Ramrao Mirgane (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Green nanoparticle synthesis is a promising, environmentally friendly, and secure method. Iron oxide nanoparticles (Fe2O3-NPs) and cobalt oxide nanoparticles (CoO-NPs) were prepared in the present research by using an aqueous flower extract of phaseolus lunatus. The prepared Fe2O3-NPs and CoO-NPs were characterized by ultraviolet-visible spectroscopy, scanning electron microscopy (SEM), dynamic light scattering (DLS), vibrating sample magnetometer (VSM), and differential scanning calorimetry (DSC). The synthesis of FeONPs was validated by the surface plasmon resonance effect. Dynamic light scattering (DLS) showed that the average particle size of FeONPs is around 163.5 nm, with a polydispersity index of 0.091 and a zeta potential of -13.8 mV. Differential scanning calorimetry (DSC) showed an endothermic peak at 176.91°C. The Vibrating Sample Magnetometer (VSM) analysis revealed that iron nanoparticles exhibit superparamagnetic properties with a magnetization value of 3.483 emu/g at room temperature, indicating their potential for use in a magnetically targeted drug delivery system. This biosynthetic approach has been demonstrated to be cost-effective, eco-friendly, and holds great potential for application in biomedical research.